Factors associated with knowledge, attitude and practice related to hepatitis B and C among international students of Universiti Putra Malaysia - Ahmad, Abdulrahman; Lye, Munn Sann; Abdul Rahman, Hejar (BioMed Central, 2016)
Background: Knowledge of hepatitis B and C has been reported to be low among respondents in different studies. We conducted a cross-sectional study among international students of Universiti Putra Malaysia (UPM) to ascertain their levels of knowledge, attitude and practices regarding hepatitis B and C and its associated factors. Methods: Six hundred and sixty two (662) international students participated in this study. A cluster sampling method was employed and data was generated using self-administered questionnaire, which was validated and its reliability checked. Results: Normality test was conducted followed by descriptive statistics, spearman's correlation and Chi-square tests to explore associations between variables in the study. The response rate was 71.49 %. Of these, 50.3 % of the respondents had better knowledge of hepatitis B; 52.7 % had better knowledge of hepatitis C; 54.8 % had positive attitude towards hepatitis B and C and 77.6 % had safer practices towards hepatitis B and C. Positive correlations were found between knowledge of hepatitis B and knowledge of hepatitis C; knowledge hepatitis B and attitude; knowledge hepatitis C and attitude; knowledge hepatitis B and practice; knowledge hepatitis C and practice; and attitude and practice regarding hepatitis B and C. Similarly, some socio-demographic variables and history of hepatitis were found to be associated with knowledge, attitude and practice related to hepatitis B and C. Conclusion: The levels of knowledge and attitude towards hepatitis B and C were low among respondents but majority of them exhibited safe practices. The study level, faculty, age, nationality, marital status and gender of the respondents were significantly associated with their levels of knowledge, attitude and practices towards the disease. These findings imply that there is need for hepatitis health promotion among the international students of UPM and possibly other international students across the globe. It will serve to improve their levels of knowledge, attitude and practices in short term and get them protected against the disease in the long run.